Unveiling CKS2: A Key Player in Aggressive B‐Cell Lymphoma Progression and a Target for Synergistic Therapy - Fenling Zhou; Lu Chen; Zhen Liu; Yuli Cao; Cuilan Deng; Gexiu Liu; Chengcheng Liu (Cancer Medicine)
ABSTRACT Background The objective of this study was to investigate the expression levels and biological significance of CKS2 in Burkitt cell lymphoma (BL) and diffuse large B‐cell lymphoma (DLBCL). Additionally, the potential synergistic anti‐tumor effects of CKS2 knockdown in combination with etoposide in BL and DLBCL were explored for the first time. Methods Bioinformatics analysis was utilized to explore the transcriptional levels, prognostic value, and gene function enrichment of CKS2 in BL and DLBCL. Specific shRNA sequences were designed to target CKS2 for the purpose of constructing a lentiviral expression vector, and therapeutic effects were assessed through analyses of cell proliferation, cell cycle distribution, and cell apoptosis. Results First, the study examined the increased transcriptional and protein levels of CKS2 in BL and DLBCL through analysis of various databases and immunohistochemistry tests. Elevated CKS2 expression was found to be correlated with a worse prognosis in BL and DLBCL patients, as evidenced by data from the TCGA and GEO databases. Enrichment analysis indicated that CKS2 functions were primarily linked to protein kinase regulatory activity, G1/S phase transition of the cell cycle, and the p53 signaling pathway, among others. Second, stable suppression of CKS2 gene expression in Raji and SUDHL6 cells using shRNA resulted in a significant inhibition of cell proliferation. Moreover, CKS2‐shRNA induced G0/G1 cell cycle arrest and apoptosis by activating the p53 signaling pathway in Raji and SUDHL6 cells. Third, the combined treatment of CKS2‐shRNA and etoposide exhibited a synergistic effect on the proliferation and apoptosis of Raji and SUDHL6 cells. Conclusions Our findings suggest that CKS2 may play a critical role in the progression of BL and DLBCL and provide evidence for the potential therapeutic application of combining CKS2‐shRNA and etoposide agents in the treatment of BL and DLBCL.